The principle of Leech's politeness in the play script Ora iso mati by Andy Sri Wahyudi - Ummaiyah, Firda; Nurhayati, Endang (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This research examines the principles of politeness contained in the play script “Ora Isa Mati.” The objective of this research is to explain the application of politeness principle and violation politeness principle in a play script "Ora Isa Mati" created by Andy Sri Wahyudi. This study falls under the category of qualitative descriptive method. The source of data is the dialogue between characters in the play script "Ora Isa Mati". The method of analyzing data using content analysis by summarizing, categorizing, and conducting a deeper analysis of the data that has been found. The result of the study indicates that there are six maxims in the application of politeness principle namely a tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. The act that contains the most application of the principle of politeness is in act one. Violations of politeness principle were found in the six maxims, namely a tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maximThe act that contains the most applications of violations of politeness is in act one. This study can be used as teaching material for learning Javanese in schools, especially in "Phase F". It is hoped that students can learn the form of the principle of politeness in the drama script.